Control of a positive output Luo-converter - Pang, Jia Wen (2015)
As the world fossil fuel reserve decreases, there has been an increase in the usage of renewable energy as an alternative source for powering up electronic devices. Since renewable energy sources generate relatively low voltages and also vary widely in magnitude. This resulted in a greater demand for more advanced DC/DC converters such as the Luo-Converter to step up the output voltage to a higher gain. These DC/DC converters are capable of converting the input voltage to a greater output voltage with higher energy density and power efficiency. This report represents the circuit design, implementation and experimental results of an Elementary Positive Output Luo-Converter to achieve a higher output voltage. An Output Feedback Controller and a Sliding-mode Controller are implemented separately to test their efficiency and performance in maintaining the output voltage of the converter and making the overall system more sustainable to interference load change. This report will present and discuss the experimental results of both open-loop and closed-loop test to show the effectiveness of the overall system under various operating parameters.